Studies of gastric aspirate nitrite, pH, bacterial flora and mutagenicity in man - Coldrey, Norman A (Division of Medical Microbiology, 2017)
Gastric aspirate specimens were collected from patients w~th clinically diagnosed gastric carcinoma and from non-carcinoma patients. The nitrite concentration and pH values of the aspirates were measured, the microorganisms present in selected specimens were isolated and identified, and the mutagenicity ratios of the aspirates were determined. The median nitrite concentration of the gastric aspirates from the carcinoma patients was significantly higher than that obtained for the non-carcinoma patients. A positive correlation was found between the nitrite concentration and the pH values of all the specimens tested, and a marked increase in nitrite levels at pH values above 6,0 was evident in specimens from the coloured ethnic "normal" subgroup. Gastric aspirate nitrite concentrations did not correlate with salivary values. The presence of microorganisms in gastric aspirates was shown to be pH dependent. Gastric aspirates with a pH < 2,0 were sterile, below pH 4,0 only acidophilic bacteria survived, whereas above pH 4,0, numerous species, predominantly members of the oral microflora, were isolated. The mean mutagenicity ratio of the gastric aspirates from the carcinoma patients was found to be significantly higher than that found for the control group. There was a positive correlation between the mutagenicity ratios of all the gastric specimens and pH with a maximum at a pH value of approximately 6,0.